2018
DOI: 10.1016/j.ijppaw.2018.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Parasite prevalence, infection intensity and richness in an endangered population, the Atlantic-Gaspésie caribou

Abstract: The Atlantic-Gaspésie caribou (Rangifer tarandus caribou) population is a small isolated relict herd considered endangered according to the Canadian Species at Risk Act (SARA). This population has low recruitment and survival rates but the potential role of parasites on individual fitness is unknown. In this context, we explored the parasite status of this population with the aim of 1) assessing the occurrence and intensity of parasite infections and the spatial, temporal and individual variations, 2) quantify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Many studies on parasitic diseases of wild mammals involve determining the parasite species composition of particular wild hosts (Bień et al 2010;Demiaszkiewicz et al 2013;Dróżdż et al 1998;Reiterová et al 2006). Due to the limited availability of wild animal carcasses, especially of protected species, studies often rely on detection of parasite eggs in mammal feces (Górski et al 2006;Szczęsna et al 2008;Turgeon et al 2018). This method, however, has limitations, including the seasonality of parasite egg shedding and difficulty in their proper identification (Hines et al 2007;Pyziel et al 2011).…”
Section: Difficulties In Parasitological Studies Of Mammals In the Wildmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on parasitic diseases of wild mammals involve determining the parasite species composition of particular wild hosts (Bień et al 2010;Demiaszkiewicz et al 2013;Dróżdż et al 1998;Reiterová et al 2006). Due to the limited availability of wild animal carcasses, especially of protected species, studies often rely on detection of parasite eggs in mammal feces (Górski et al 2006;Szczęsna et al 2008;Turgeon et al 2018). This method, however, has limitations, including the seasonality of parasite egg shedding and difficulty in their proper identification (Hines et al 2007;Pyziel et al 2011).…”
Section: Difficulties In Parasitological Studies Of Mammals In the Wildmentioning
confidence: 99%
“…It has been suggested that individuals in poor condition could be a Bbad choice^for parasites due to the lack of available resources (Bize et al 2008; Schulte-Hostedde and Elsasser 2011). However, parasites may negatively influence the body condition of their hosts (Turgeon et al 2018;Winternitz et al 2012), e.g., mink body condition has been negatively associated with nematode abundances in the gastrointestinal tract (Kołodziej-Sobocińska et al 2018a). The deterioration of the body condition may be accelerated because individuals in poor condition are unable to control parasitic infection by mounting sufficient immune defenses (Martin et al 2003).…”
Section: Body Condition Health and Immunocompetencementioning
confidence: 99%
“…For instance, parasite load has inherent links to both species diversity and abundance in a range of host systems (Main & Bull 2000;Godfrey 2013;Gómez & Nichols 2013). The spatial and social construction of a population provides opportunities for a myriad of direct or indirect transmission of parasites (Lumbad et al 2011;Turgeona et al 2018). For instance, network connectivity, by way of refuge sharing in sleepy lizards (Tiliqua rugosa), has been demonstrated to facilitate the indirect transmission of an ectoparasitic tick (Amblyomma limbatum; Leu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, and to be consistent with epidemiological terminologies, the intensity of the infection is defined as the mean number of EPG or OPG of feces calculated over all samples tested positive for the parasite, intensity is zero when a host has no GIP [49,50]; this contrasts with the definition suggested by Bush et al [51]. Anemia can be classified according to cell size (normocytic, microcytic, or macrocytic, indicating normal, increased, or decreased PCV, respectively) and to Hgb concentration (normochromic, hypochromic, or hyperchromic, indicating normal, decreased, or increased Hgb concentration, respectively) [52,53].…”
Section: Discussionmentioning
confidence: 99%